2021
DOI: 10.1002/ijgo.13620
|View full text |Cite
|
Sign up to set email alerts
|

Repeat induced abortion in 30 Chinese provinces: A cross‐sectional study

Abstract: Objective: To report the proportion and determinants of repeat induced abortions in China. Methods: Cross-sectional data were collected of 79 954 women who received an induced abortion from 297 hospitals across 30 Chinese provinces in 2013, using a stratified cluster sampling design. Logistic and Poisson regression models were fitted to identify characteristics associated with repeat abortion. Putative factors included age, household registration (hukou) status, marital status, education, occupation, reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…The analysis revealed that women aged 25-34 years represented 53.1% of the pre-COVID group versus 43.5% among this study group (0.01<p<0.05). Marital status was similar (68.2% in the pre-COVID group vs 64.4%, p>0.05) as were the proportion of women who had children (57.3% pre-COVID vs 52.6%, p>0.05) [52]. The mean gestational age of participating women was 43.7±6.2days ~ 59.0±14.5 days in previously published studies [53][54][55], compared to 51±7.3 days in the current study.…”
Section: Limitationssupporting
confidence: 52%
“…The analysis revealed that women aged 25-34 years represented 53.1% of the pre-COVID group versus 43.5% among this study group (0.01<p<0.05). Marital status was similar (68.2% in the pre-COVID group vs 64.4%, p>0.05) as were the proportion of women who had children (57.3% pre-COVID vs 52.6%, p>0.05) [52]. The mean gestational age of participating women was 43.7±6.2days ~ 59.0±14.5 days in previously published studies [53][54][55], compared to 51±7.3 days in the current study.…”
Section: Limitationssupporting
confidence: 52%
“…In terms of repeat induced abortion, 30.83% of the women in this study had experienced repeat abortions, a lower percentage than that reported in previous research. Many studies have argued that the repeat induced abortion incidence rate is very high in China [ 18 , 19 , 35 ]. A study involving 79,954 women who underwent induced abortion operations in 297 hospitals in 30 provinces in China showed that 65.2% of all induced abortions were repeat induced abortions [ 19 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Education level also affects women’s induced abortion behaviors in China [ 9 , 11 , 17 ], although research conclusions diverge in this area. Some studies have shown that less-educated women have less knowledge of reproductive health and contraception and are more likely to undergo induced abortion and repeat induced abortions [ 12 , 18 , 19 ]. However, other studies have shown that women with higher levels of education have higher abortion rates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis revealed that women aged 25–34 years represented 53.1% of the pre-COVID group versus 43.5% among this study group (0.01 < p < 0.05). Marital status was similar (68.2% in the pre-COVID group vs 64.4%, p > 0.05) as were the proportion of women who had children (57.3% pre-COVID vs 52.6%, p > 0.05) [ 52 ]. The mean gestational age of participating women was 43.7 ± 6.2 days ~ 59.0 ± 14.5 days in previously published studies [ 53 55 ], compared to 51 ± 7.3 days in the current study.…”
Section: Discussionmentioning
confidence: 99%